Evaluasi Advokasi Penyelesaian Konflik Sengketa Tanah di Kabupaten Banggai, Sulawesi Tengah - BADRAH, ADRIANY (Universitas Muhammadiyah Yogyakarta, 2011)
This research aims to determine the extent to which advocacy is conducted by Front Rakyat AdvokasiSawit (FRAS) for the handling of conflict in Central Sulawesi land disputes between famers Toili andPT Kurnia Luwuk Sejati (PT KLS). The background of this research is about the conflict of landdisputes between farming communities Toili with PT KLS in Banggai regency of Central Sulawesiprovince. This study uses the method of evaluation that is part of the decision making process, namelyto compare an event, activity has been determined. This study uses qualitative analysis and data types.Qualitative research aims to describe and analyze problems that become the object of this study as anevaluation of the advocacy process, so this study can give an idea about advocacy in conflict resolutionof land disputes and the factors surrounding the advocacy process to determine the success or failure ofadvocacy efforts related to resolving conflicts and land disputes Toili farmers PT KLS.